A green separation process of Ag via a Ti4(embonate)6 cage. Issue 47 (13th November 2020) - Chen, Guang-Hui; He, Yan-Ping; Liang, Fu-Pei; Zhang, Lei; Zhang, Jian
Abstract : A green supramolecular recovery process of Ag has been developed by using a highly charged anionic Ti4 L6 (L = embonate) cage as the extractant. Abstract : From an environmental perspective, silver recovery through a green process is imperative. In this work, a green supramolecular separation process of Ag has been developed by using a highly charged anionic Ti4 L6 (L = embonate) cage as the extractant. Such a Ti4 L6 cage has unique selectivity toward [Ag(NH3 )2 ] + ions, because only linear [Ag(NH3 )2 ] + ions can be trapped into the windows of the Ti4 L6 cage, which is demonstrated by single-crystal X-ray diffraction analysis. To further illustrate the efficiency and mechanism of the herein constructed silver separation method, three co-crystals of the Ti4 L6 cage with various [Ag(NH3 )2 ] + ions were prepared and structurally characterized, annotating the stepwise recognition of [Ag(NH3 )2 ] + ions by the Ti4 L6 extractant. However, it failed to trap larger tetrahedral [Zn(NH3 )4 ] 2+ and quadrilateral [Pb(NH3 )4 ] 2+ ions under the same reaction conditions, indicating that configuration matching contributes to the high selectivity of the above-mentioned silver separation procedure. More interestingly, Ag nanoparticles with high yield could be obtained by the reduction of the [Ag(NH3 )2 ]&Ti4 L6 extracts with hydrazine hydrate (N2 H4 ·H2 O), and the Ti4 L6 cages can be readily recycled through recrystallization. This discovery offers a green supramolecular procedure for silver recovery with coordination cages as efficient and recyclable extractants.